Gender equity in Brazilian rheumatology (Reuma Equity): a cross-sectional survey study. (September 2022) - Peixoto Souza, Mariana; Souza, Viviane Angelina; Rotsen, Thais; Guimarães, Maria Fernanda; Ovseiko, Pavel; Coates, Laura; Wright, Grace; Monticielo, Odirlei; Xavier, Ricardo; Kakehasi, Adriana
Abstract: Background: Knowledge on the status of gender equity in academic and clinical rheumatology in Brazil is scarce. Here, we aimed to create a scenario of work possibilities, academic development, and social issues among Brazilian rheumatologists. Methods: This cross-sectional study was done using a web-based survey conducted among members of the Brazilian Society of Rheumatology. The survey consisted of 33 questions divided into five domains (academic sociodemographic, work performance, family, gender inequity or harassment, and improvement possibilities). Gender was self-reported as woman, man, or other. Descriptive analysis was performed, assessing responses from women and men, by Pearson χ 2 . Age was measured as a categorical variable stratified into 5-year intervals. Findings: Between Oct 2, 2021, and July 26, 2022, the survey was completed by 459 (22%) of 2118 Brazilian Society of Rheumatology members. Most participants were women (308 [67%] vs 151 [33%] men; p<0·0001). Women were more frequently younger, particularly in the 32–46 years age group (163 [53%] vs 57 [38%]; p=0·001), and men were more frequently older than 57 years (64 [21%] vs 61 [40%] women; p=0·001). More women worked in the public service (119 [39%] vs 36 [24%] men; p=0·002), had longer appointment durations (more than 45 min; 115 [37%] vs 45 [30%]; p=0·01), and worked less than 45 h per week (176 [57%] vs 76 [50%]; p=0·008). Women were most affected in family and work relationships (eg, changing career due to family demands; 247 [80%] vs 100 [66%]; p=0·001); had a greater house and family workload (185 [60%] vs 16 [11%]; p=0·001); and were more exposed to verbal (137 [44%] vs 25 [17%]; p<0·0001), non-verbal (166 [54%] vs 29 [19%]; p<0·0001), and physical sexual harassment (74 [24%] vs 17 [11%]; p=0·005). A lower percentage of women participated in the Brazilian Society of Rheumatology (276 [47%] of 671 vs 202 [62%] of 324 men; p<0·0001), and more women believed there is a gender gap in the work environment (178 [58%] vs 59 [39%] men; p=0·001) and a need for interventions in this field (233 [76%] vs 75 [50%] men; p<0·0001). No significant difference was observed in postgraduate degrees (148 [48%] vs 67 [44%]; p=0·17), leadership positions (122 [40%] vs 71 [47%]; p=0·13), and the frequency of medical consultation fees higher than R400 (95 [31%] vs 64 [42%]; p=0·058). Women also had and same career satisfaction as men (243 [79%] vs 120 [79%]; p=0·082) and higher self-confidence (202 [66%] vs 81 [54%]; p=0·007). Interpretation: Despite the fact that women have reached the same level of academic development and work capacities, inequality persists in scientific recognition and social aspects. This study identified several opportunities of interventions for an improved gender balance in Brazilian rheumatology. Funding: None.